Effect of cDMEM media containing Ectoine on human periodontal ligament mesenchymal stem cell survival and differentiation - AKKOÇ, TUNÇ (My University, 2018)
Background/Aim: Ectoine is an amino acid that can preserve osmotic balance and has more preservative activity than other osmoregulators. There are no published reports on the osmoregulators’ effects on viability or differentiation of dental stem cells. The aim of this study was to investigate the effect of Ectoine as a storage media on the viability and differentiation potential of human periodontal ligament mesenchymal stem cells (hPDLMSCs). Materials and Methods: hPDLMSCs were obtained from impacted third molar teeth. The cells were isolated, submitted to trilineage differentiation, and characterized by flow cytometer (FC). hPDLMSCs were incubated with different media containing Ectoine, complete DMEM (cDMEM), Ectoine+cDMEM, milk, and tap water for 2, 6, 12, and 24 h. The cells were analyzed by FC for viability, early-apoptosis, late apoptosis, and necrosis rates. Osteogenic and fibroblastic differentiation in hPDLMSCs were investigated by Alizarin red stain and vimentin expression. Results: All treated groups showed significant decreases in cell viability after 2 h. Significant increases were detected in the number of dead cells between 2 and 12 h in all groups except the Ectoine+cDMEM group. The deposition of mineral matrix nodules was significantly higher in cells cultured with Ectoine+cDMEM compared with the other media. Higher vimentin expressions were detected in cells cultured with cDMEM and Ectoine+cDMEM media, respectively. Conclusions: Ectoine added to cDMEM media, promoted cell survival plus osteogenic and fibroblastic differentiation of hPDLMSCs.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; cell viability; ectoine; fibroblastic differentiation; osteogenic differentiation; periodontal ligament cells; TRAUMATIC DENTAL INJURIES; STORAGE MEDIA; IN-VITRO; AVULSED TEETH; GROWTH-FACTORS; STROMAL CELLS; COCONUT WATER; VIABILITY; MILK; PLASTICITY; cell viability; ectoine; fibroblastic differentiation; osteogenic differentiation; periodontal ligament cells